2000
DOI: 10.1094/pdis.2000.84.8.843
|View full text |Cite
|
Sign up to set email alerts
|

Geminiviruses Infecting Tomato Crops in Nicaragua

Abstract: Geminiviruses transmitted by whiteflies are believed to be responsible for the devastating epidemic in tomato crops in Nicaragua, as well as in other Central American countries. Polymerase chain reaction with degenerate primers was used to amplify partial sequences of the geminivirus coat protein gene from samples of diseased tomato plants collected from the major tomato-growing areas of Nicaragua. The data indicated the presence of geminiviruses in all tested regions of the country. DNA sequence analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 16 publications
0
30
0
2
Order By: Relevance
“…The virus also infected Nicotiana benthamiana , producing leaf curling and mosaic symptoms 2 weeks after mechanical inoculation. PCR products were generated using generic primers (Deng 540/541 [Deng et al ., 1994] and prV324/C889 [primers referenced in Rojas et al ., 2000]) to component A of begomoviruses and sequenced. Specific primers (ToMHV F1 GCAAATACGAGAATCATACTGAG and ToMHV R2 CAATTGTACGGAAAGAGGAAAGG) were designed to obtain the complete sequence of 2619 nucleotides of component DNA A (GenBank EF088197).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The virus also infected Nicotiana benthamiana , producing leaf curling and mosaic symptoms 2 weeks after mechanical inoculation. PCR products were generated using generic primers (Deng 540/541 [Deng et al ., 1994] and prV324/C889 [primers referenced in Rojas et al ., 2000]) to component A of begomoviruses and sequenced. Specific primers (ToMHV F1 GCAAATACGAGAATCATACTGAG and ToMHV R2 CAATTGTACGGAAAGAGGAAAGG) were designed to obtain the complete sequence of 2619 nucleotides of component DNA A (GenBank EF088197).…”
mentioning
confidence: 99%
“…Two small partial sequences from Jamaica (AF035224 and U82829) also aligned with more than 90% identity. ToMHV was first identified and sequenced in Cuba and found to be a distinct begomovirus (Martinez Zubiaur et al ., 1998 (Rojas et al ., 2000;Ala-Poikela et al ., 2005). However, these surveys failed to detect ToMHV.…”
mentioning
confidence: 99%
“…This indicated that the Begomovirus infecting legumes are entirely distinct from the Begomoviruses infecting other crops. (Muniyappa et al, 2003;Rojas, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Las altas o bajas poblaciones de mosca blanca en parcelas de tomate, están influenciadas por condiciones ambientales como temperatura, humedad relativa, y precipitación (Hilje,1993) así como también por las características genéticas que posea la variedad a cultivar (Rojas et al, 2000); por tal razón, se puede mencionar que las poblaciones de este insecto no siempre se comportan de forma similar en todas las parcelas. Existe una gran diferencia en lo que son insectos plagas e insectos vectores por lo tanto sus poblaciones deben ser manejadas de forma diferente, razón por la cual muchos de estos insectos se han convertido en serio problema para la agricultura (Jiménez-Martínez, 2008).…”
Section: Discussionunclassified